Presumed intimacy parasocial interaction in media, society and celebrity culture - Rojek, Chris (Polity Press, 2016)
"This engaging book examines how the ease with which modern social and media networks create a sense of intimacy which can be exploited by media, politicians and authoritarian intriguing thesis on how media creates relations where we are constant watchers of the lives of others.